PERWALIAN ANAK DI LUAR PERKAWINAN DALAM PERSPEKTIF MAZHAB SYAFI’I DAN HANAFI: ANALISIS FIQH PERBANDINGAN DAN IMPLIKASINYA TERHADAP HUKUM KELUARGA ISLAM - Aniqotul Fitriyah; Ita Rahmania Kusumawati (LPPM STAI Muhammadiyah Probolinggo, 2026)
Marriage according to Islam is an act of worship with a very strong contract to obey God's commands and carry them out with a chosen partner. This study discusses the guardianship of children born out of wedlock to determine whether they are related to their father or not by comparing the differences of opinion between the Shafi'i and Hanafi schools of thought. Using descriptive literature research and a qualitative approach, the researcher attempts to explain the differences between the Shafi'i and Hanafi schools of thought regarding the guardianship of children born out of wedlock. The Shafi'i school considers a guardianship as a valid pillar of marriage. Therefore, an illegitimate child who does not have a guardian through his father requires a legal guardian to marry him because he does not have a lineage to his biological father. On the other hand, the Hanafi school of thought states that a guardian is not an absolute requirement, so an adult and sane woman can marry herself without a guardian.